KEPUASAN PENGUNJUNG TEMPAT WISATA PEMANDIAN HAIROS WATERPARK MEDAN - Amanah, Dita; Budiarta, Kustoro; Harahap, Dedy Ansari (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2018)
This article analyzes the satisfaction of visitors to the tourist attractions of Hairos Waterpark Medan. The sample in this study was 90 respondents with a purposive sampling as a sampling technique that is only addressed to respondents who have made visit to Hairos Waterpark. Data analysis technique used is a simple linear regression because it only analyzed service quality to the visitor satisfaction in Hairos Waterpark. The regression result was Y = 3.006 + 0.269X + e. The t test result was 3.452 and the coefficient of determination was 0.119. These results indicate that service quality positively and significantly influence to the visitor satisfaction in Hairos Waterpark Medan. Therefore, Hairos Waterpark management really needs to consider the quality of service in influencing people to visit Hairos Waterpark and further affecting visitors satisfaction. Limitations and suggestions are also discussed in this article. Keywords: Service Quality, Satisfaction, Waterpark, Simple Linear Regression